Pengaruh Penggunaan Pembayaran Digital Terhadap Minat Mahasiswa Menggunakan Quick Response Code Indonesian Standard (QRIS) Pada Program Studi Manajemen Bisnis Syariah UMSU - Dea Adilla Elsa; Isra Hayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to evaluate the impact of using digital payments on student interest in using the Indonesian Standard Quick Response Code (QRIS) in the UMSU Sharia Business Management Study Program. This research method carries a quantitative approach with the main data obtained through the use of questionnaires, where the sample size reached 78 respondents. Data analysis was carried out using SPSS version 26 software, with the application of the (t) test technique and simple linear regression analysis. The results of the partial test (t) show that the payment usage variable has a significant influence on the student interest variable in using QRIS. With a tcount value of 9.964 > ttable of 1.992, it can be concluded that the Use variable (X) has an effect on the Interest variable (Y). In addition, based on the R2 test results, it was concluded that the impact of the independent variable (Use) on the dependent variable (Interest) reached 56.6%. Keywords: Digital, Interest and QRIS